Prognostic Role of Histological Tumor Regression in Patients Receiving Neoadjuvant Chemotherapy for High-Grade Serous Tubo-ovarian Carcinoma. Issue 4 (1st May 2017) - Coghlan, Edwina; Meniawy, Tarek M.; Munro, Aime; Bulsara, Max; Stewart, Colin JR; Tan, Adeline; Koay, MH Eleanor; MaGee, Daniel; Codde, Jim; Tan, Jason; Salfinger, Stuart G.; Mohan, Ganendra R.; et al.
Abstract : Objective: Our objective was to validate the prognostic role of the chemotherapy response score (CRS), which has been proposed for measuring tumor response to neoadjuvant chemotherapy in patients with high-grade serous tubo-ovarian carcinoma, in predicting progression-free survival (PFS) and overall survival (OS). Methods: A retrospective cohort study was conducted of patients with advanced high-grade serous tubo-ovarian carcinoma diagnosed between January 1, 2010, and December 31, 2014, and treated with neoadjuvant chemotherapy. Treatment-related tumor regression was determined according to the 3-tier CRS, and results were compared with standard clinicopathological variables. Survival analysis was performed using Cox proportional hazards models and the log-rank test. Results: Seventy-one patients were eligible for analysis. Median OS was 25.5 months. Fifty-eight patients (82%) had disease recurrence and 32 (45%) had died at study census. Of the 71 patients, 19, 29, and 23 patients had a CRS of 1, 2, and 3, respectively. On univariate analysis, the CRS significantly predicted PFS (hazard ratio [HR], 3.77; 95% confidence interval [CI], 1.83–7.78; P = 0.000) and OS (HR, 2.81; 95% CI, 1.16–6.79; P = 0.022). In a multivariate model, the CRS was significantly associated with PFS (HR, 2.81; 95% CI, 1.16–6.79; P = 0.022) but not with OS (HR, 2.39; 95% CI, 0.47–3.08; P = 0.079). Patients with CRS of 1 and 2 combined were twice as likely to progress during the study period compared with patients with a CRS of 3 (HR, 2.0; 95% CI, 1.06–3.78; P = 0.032; median PFS, 16 vs 26 months). No significant association was observed for OS (CRS 1/2 vs 3; HR, 1.57; 95% CI, 0.68–3.65; P = 0.291). Conclusions: In this study, the CRS showed independent prognostic significance for PFS but not for OS.